2002
DOI: 10.1046/j.1469-0691.2002.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Enterobacteriaceae to β-lactam agents and fluoroquinolones: a 3-year survey in France

Abstract: Over the 3-year study period beta-lactams and fluoroquinolones remained highly active against Enterobacteriaceae clinical isolates, with the exception of E. aerogenes, probably as a result of the dissemination of multiresistant clones in French hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The increased incidence of bacterial resistance to antimicrobial agents in both nosocomial and community settings requires careful thought. A French prospective study with 320 E. coli strains isolated from urinary tract infections between 1998 and 1999 showed that the prevalence of resistance to amoxicillin was 46.1% (31). Gupta et al showed that the prevalence of antimicrobial resistance among uropathogens causing acute uncomplicated cystitis in women is also increasing (14).…”
Section: Discussionmentioning
confidence: 99%
“…The increased incidence of bacterial resistance to antimicrobial agents in both nosocomial and community settings requires careful thought. A French prospective study with 320 E. coli strains isolated from urinary tract infections between 1998 and 1999 showed that the prevalence of resistance to amoxicillin was 46.1% (31). Gupta et al showed that the prevalence of antimicrobial resistance among uropathogens causing acute uncomplicated cystitis in women is also increasing (14).…”
Section: Discussionmentioning
confidence: 99%
“…While ESBLs were initially found mainly in Klebsiella pneumoniae and Escherichia coli, an increasing variety of gram-negative species have been shown to harbor such resistance mechanisms (7,8). In recent years, ESBLs have become more prevalent in AmpC-producing species (1,16). In spite of the worldwide use of ␤-lactam antimicrobial agents, which is considered the main reason for the emergence of ESBLs (2), the distributions of ESBLs are far from uniform.…”
mentioning
confidence: 99%
“…Extended-spectrum beta-lactamases (ESBLs) are important enzymes that cause resistance to extended-spectrum cephalosporins in the widespread pathogens Klebsiella, Escherichia, Proteus, and Enterobacter (1,27,28); rarely in other members of the family Enterobacteriaceae; and sporadically in nonfermentating gram-negative bacilli such as Pseudomonas and Acinetobacter spp. (38,39).…”
mentioning
confidence: 99%